Reciclagem da borracha: uma análise sobre os processos e impactos ambientais - Souza, Mikaela Mikaeza Brandão de (Brasil, 2024)
Natural rubber (NR) plays an essential role in contemporary society, especially in industry, where it is widely used, mainly in the production of automobile tires. Its elasticity is a fundamental property, derived from the connections between polymer chains, giving it monetary characteristics. Vulcanization, a chemical and structural procedure, reinforces the rubber's resistance to tension, abrasions and temperature variations, transforming it into an elastic material capable of recovering its original shape after deformation. However, the recycling of vulcanized rubber faces challenges due to the complexity of undoing the connections between the chains, making it difficult to reuse it as a raw material. This scenario has driven efforts to develop recycling technologies, reducing the environmental, social and economic impacts of the accumulation of unusable tires. Recycling natural rubber can involve processes that break connections between chains, resulting in value-added materials that can be reintegrated into new rubber formulations. This study seeks to explore the main rubber recycling methods, detailing their characteristics, benefits and challenges. Furthermore, a Life Cycle Assessment (LCA) was carried out to compare the environmental impacts of energy recycling of different types of rubber.